Prospect and progress of personalized peptide vaccinations for advanced cancers. (3rd May 2016) - Sakamoto, Shinjiro; Noguchi, Masanori; Yamada, Akira; Itoh, Kyogo; Sasada, Tetsuro
ABSTRACT: Introduction : The field of cancer immunotherapy has made dramatic progress in the past 20 years, in part due to the identification of numerous tumor-associated antigens (TAAs). We have developed a novel immunotherapeutic approach called the personalized peptide vaccine (PPV), in which a maximum of four human leukocyte antigen (HLA)-matched vaccine peptides are selected based on the pre-existing host immunity before vaccination. Areas covered : This review describes recent progress in the use of PPV for various types of advanced cancer. Expert opinion : Although various approaches for therapeutic cancer immunotherapies, including peptide-based vaccines, have been developed and clinically examined, the diverse and heterogeneous characteristics of tumor cells and host immunity seem to limit their therapeutic efficacy. Selection of suitable peptide vaccines for individual patients based on the pre-existing host immunity before vaccination could resolve this limitation and could be a rational approach for developing effective cancer vaccines.